Análisis bacteriológico de la clínica de ortodoncia del Posgrado de la Facultad de Odontología - Martínez Fantini Guillén, Tonatiuh (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The daily care of patients in dental clinics carry a high risk of cross contamination for the patient, the dentist and to the entire workforce; starting from the parameters required by the official Mexican standards and the need for a study of this type for certifications and institutional assessments, the corresponding protocol is proposed for bacteriological analysis in the clinic of the Faculty of Graduate Dentistry. General Objective: To propose a protocol to determine the risk of cross contamination that exists in the orthodontic clinic of Graduate School of Dentistry, Universidad Michoacana de San Nicolás de Hidalgo. Methods: By reviewing articles from 1990 to 2011 , have allowed to evaluate the various methodologies and also can perform processing and propose a protocol to recognize if there is a risk of bacterial contamination in clinical orthodontics graduate orthodontic faculty of dentistry. Results: The proposed protocol was to select various surfaces for sampling , the handle of the lamp, the table in May, and the delivery area of material; sampling in 4 times in the morning before the first round , at the end of the first turn, before the second round after cleaning , and end of the day. Samples were transported to the laboratory for culture and analysis for parameters defined as existence of bacterial strains, colony forming units, genus and species identification and pathogenicity of colonies found. Conclusions: It was possible to establish the protocol that will determine the level of contamination and type of bacteria in the graduate orthodontic clinic of the graduate faculty of dentistry. Through the methodology used by Guihan Lee in 2011. Said conceives effective protocol to determine different levels of bacterial contamination, and identify different types of microorganisms counts and their pathogenicity.

Las atenciones diarias de pacientes en las clínicas dentales conllevan un alto riesgo de contaminación cruzada tanto para el paciente, el odontólogo, así como para todo el personal laboral; partiendo de los parámetros que exigen las normas oficiales mexicanas y la necesidad de un estudio de este tipo para certificaciones y evaluaciones institucionales, se propuso el protocolo correspondiente para realizar un análisis bacteriológico en la clínica del posgrado de la Facultad de Odontología. Objetivo General: Proponer un protocolo que permita determinar el riesgo de contaminación cruzada que existe en la clínica de ortodoncia del Posgrado de la Facultad de Odontología de la Universidad Michoacana de San Nicolás de Hidalgo. Materiales y métodos: Mediante la revisión de artículos del año 1990 hasta el 2011, han permitido poder evaluar las distintas metodologías y así poder llevar a cabo la elaboración y propuesta de un protocolo que permita reconocer si existe riesgo de contaminación bacteriana en la clínica ortodoncia del posgrado de ortodoncia de la UMSNH. Resultados: El protocolo propuesto consistió en seleccionar distintas superficies para realizar la toma de muestras, el maneral de la lámpara, la mesa de mayo, y el área de entrega de material; tomando muestras en 4 tiempos, por la mañana antes del primer turno, al final del primer turno, antes de comenzar el segundo turno después de la limpieza, y al final de la jornada. Las muestras se transportarán al laboratorio para su cultivo y análisis en cuanto a parámetros definidos como existencia de cepas bacterianas, unidades formadoras de colonias, identificación de género y especie y grado de patogenicidad de las colonias encontradas.
Facultad de Odontología. Especialidad en Ortodoncia
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4563; info:eu-repo/classification/cti/3; FO-E-2014-0829; Análisis bacteriológico; Contaminación; Clínica